2022
DOI: 10.1177/10556656221130829
|View full text |Cite
|
Sign up to set email alerts
|

Does Differential Maxillary Expansion Prior to Alveolar Cleft Bone Grafting Affect Nasal Width?

Abstract: Objective Determine the effects of differential maxillary expansion on nasal width in patients with unilateral cleft lip and alveolus with or without cleft of the secondary palate (UCLA ± P). Design Retrospective radiographic study. Setting Institutional. Participants Forty patients with UCLA ± P who had alveolar bone grafting (ABG) between 2015 and 2020 and available preexpansion and postexpansion cone beam computed tomography (CBCT) scans. Twenty patients with UCLA ± P who underwent ABG without expansion wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…At least one study showed widening of the nasal width with maxillary expansion compared with patients who underwent ABG without expansion. 7 This expansion may work in the patient benefit with a narrow cleft side but, more often, may worsen the asymmetry with those with an already wide alar base.…”
Section: Alveolar Bone Graftmentioning
confidence: 99%
“…At least one study showed widening of the nasal width with maxillary expansion compared with patients who underwent ABG without expansion. 7 This expansion may work in the patient benefit with a narrow cleft side but, more often, may worsen the asymmetry with those with an already wide alar base.…”
Section: Alveolar Bone Graftmentioning
confidence: 99%